PENGARUH PROFITABILITAS, LEVERAGE, DAN LIKUIDITAS TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BEI - Willi Matulesi Sibarani; Rahima Boru Purba; Puja Rizqy Ramadhan (Ensiklopedia Education Review, 2021)
Conceptually, the tax avoidance scheme is actually legal or legal because it does not violate tax provisions. Although basically there is a tax avoidance practice that is considered legal or does not deviate from the law, this practice can still harm the state. This study aims to determine the effect of profitability, leverage, and liquidity on tax avoidance in manufacturing companies on the Indonesia Stock Exchange for the 2018-2020 period. This research is a type of associative research. The population in this study are manufacturing companies in the various industrial sectors on the Indonesia Stock Exchange for the 2018-2020 period with a total of 52 companies with a sample of 12 companies. The sampling technique is purposive sampling. The data collection technique uses documentation from financial reports published on the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The analysis used is using panel data regression analysis which was tested with the F test and t test, with a significant level of 5%. The results of this study indicate that profitability and liquidity have a negative effect on tax avoidance, while leverage has no effect on tax avoidance. This research is expected to help academics and further researchers as a reference material. Keywords: Tax Avoidance, Liquidity, Leverage, Profitability.